Women's textile pattern designs based on the principle of geometric perspective / Zhu Ziwei ... [et al.] - Zhu, Ziwei; Aris, Asliza; Li, Zifei; Ahmad, Hasma (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
Geometric perspectives, derived from mathematical principles, is a technique that combines science and art by applying perspective to painting. Geometric perspectives are divided into three categories, namely: one-point perspective, in which there is only one perspective vanishing point in the structure of the perspective, which can show a sense of three dimensionality; angular perspective, which can bring a sense of space; and a three-point perspective, which is an aggregate of the two. Geometric elements in modern fashion design are developed from the traditional art of geometric patterns. With the rise of different disciplines and the birth of theories, as well as the artistic exploration of geometric elements by designers, geometric elements have been applied in a variety of ways in clothing design. In specific clothing design, designers can express geometric elements as integral content, or as local decorative designs to be integrated into the overall design. Based on the three categories of geometric perspective, this study explores the effects of its application in modern textile patterns respectively and analyses their functions on the clothing as a whole, such as the effect of the optical illusion caused by geometric perspectives in clothing, the expression of linear changes, and the forms of application of the elements of points, lines and planes therein. This research analyses and collates these through a case study approach, and then through a practical research approach, using Photoshop to design three clothes, using the clothing plane renderings to show the effects of each of the three categories of geometric perspectives as they are applied to the textile surface patterns. This study aims to achieve figure modification through the use of simple geometric patterns on textiles. Textile patterns can visually refine the body shape rather than through functional clothing such as corsets, which is conducive to alleviating women's body shame while protecting their health.